Self-assembled hexanuclear arene ruthenium metallo-prisms with unexpected double helical chirality - Govindaswamy, Padavattan; Linder, David; Lacour, Jerôme; Süss-Fink, Georg; Therrien, Bruno (My University, 2006)
Self-assembly of 2,4,6-tripyridyl-1,3,5-triazine (tpt) subunits with arene ruthenium building blocks and oxalato bridges affords cationic triangular metallo-prisms of the type [Ru6 (arene) 6 (tpt)2 (C2O4)3]6+ (arene = C6Me6 and p-PriC6H4Me); the unexpected double helical chirality of the metallo-prisms observed in the solid state persists in solution giving rise to two different stereodynamic processes as demonstrated by NMR enantiodifferentiation experiments.